2009
DOI: 10.1121/1.3087435
|View full text |Cite
|
Sign up to set email alerts
|

Release from informational masking in children: Effect of multiple signal bursts

Abstract: This study examined the degree to which increasing the number of signal presentations provides children with a release from informational masking. Listeners were younger children ͑5-7 years͒, older children ͑8-10 years͒, and adults. Detection thresholds were measured for a sequence of repeating 50-ms bursts of a 1000-Hz pure-tone signal embedded in a sequence of 10-and 50-ms bursts of a random-frequency, two-tone masker. Masker bursts were played at an overall level of 60-dB sound pressure level in each interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Reductions in informational masking with increasing age during childhood have also been reported in the literature (Leibold and Bonino, 2009;Leibold and Neff, 2007;Lutfi et al, 2003b;Wightman et al, 2003). For example, 8-to 10-yr-old children have better thresholds than 5-to 7-yr-old children for the detection of a tone in the presence of a random-frequency, multi-tonal masker (Leibold and Neff, 2007;Leibold and Bonino, 2009). Despite improvements in performance with increasing age during childhood, significant child-adult differences have been observed as late as adolescence for the detection of a pure-tone signal embedded in a random-frequency, multitonal masker (Lutfi et al, 2003b;Wightman et al, 2003).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Reductions in informational masking with increasing age during childhood have also been reported in the literature (Leibold and Bonino, 2009;Leibold and Neff, 2007;Lutfi et al, 2003b;Wightman et al, 2003). For example, 8-to 10-yr-old children have better thresholds than 5-to 7-yr-old children for the detection of a tone in the presence of a random-frequency, multi-tonal masker (Leibold and Neff, 2007;Leibold and Bonino, 2009). Despite improvements in performance with increasing age during childhood, significant child-adult differences have been observed as late as adolescence for the detection of a pure-tone signal embedded in a random-frequency, multitonal masker (Lutfi et al, 2003b;Wightman et al, 2003).…”
Section: Introductionmentioning
confidence: 79%
“…These masking effects tend to be pronounced during childhood, with child-adult differences as large as 50 dB (e.g., Oh et al, 2001). Reductions in informational masking with increasing age during childhood have also been reported in the literature (Leibold and Bonino, 2009;Leibold and Neff, 2007;Lutfi et al, 2003b;Wightman et al, 2003). For example, 8-to 10-yr-old children have better thresholds than 5-to 7-yr-old children for the detection of a tone in the presence of a random-frequency, multi-tonal masker (Leibold and Neff, 2007;Leibold and Bonino, 2009).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although NH children are able to use spatial cues for source segregation, developmental effects have been reported in free field Yuen and Yuan, 2014) and for contralateral unmasking headphone stimulations (Wightman and Kistler, 2005). This difference could be due to the fact that informational masking also depends on development of central auditory mechanisms and nonauditory factors such as attention (Leibold and Bonino, 2009;Lutfi et al, 2003;Wightman et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…It is known that auditory pathways continue to mature into adolescence (Boothroyd, 1997). Specific to this study, informational masking has been shown to have a developmental component (Leibold and Bonino, 2009;Wightman and Kistler, 2005). Wightman et al (2010) tested NH populations ages 5 to 61 and showed that the most variability on a dichotic listening task involving informational masking was observed in NH children ages 6 to 12 years of age.…”
Section: B Effects Of Interferer Locationmentioning
confidence: 99%